Induced sputum and other outcome measures in chronic obstructive pulmonary disease: safety and repeatability. - Brightling, C; Monterio, W; Green, R; Parker, D; Morgan, MD; Wardlaw, A; Pavord, D (2001)
The forced expiratory volume in 1 sec (FEV1) is the most established outcome measure in chronic obstructive pulmonary disease (COPD). However, changes in FEV1 in response to treatment are small in relation to the repeatability of the measurement and there is increasing interest in other measures including markers of lower airway inflammation in induced sputum, assessment of symptoms and health status using visual analogue scores, and questionnaires. Little is known about the repeatability of these measures or the safety of sputum induction in COPD. We have assessed the safety of sputum induction in 61 subjects with moderate and severe COPD who participated in a placebo-controlled cross-over study The within-subject repeatability of sputum markers of airway inflammation, health status using the chronic respiratory disease questionnaire (CRQ) and symptom visual analogue scores (VAS) were estimated from the data obtained from before and after 2 weeks of treatment with placebo. Sputum induction was performed on 122 occasions and was successful resulting in a cytospin adequate to assess a differential cell count in 95% of inductions. The group mean (SEM) FEV1 was 1.09 (0.05)[41.6 (2.9)% predicted] and the mean (SEM) fall in FEV1 after sputum induction was 120 ml (6) and % fall 10.9% (0.55%). Seven inductions were stopped due to a fall in FEV1 >20% and at a further 13 visits the full sputum induction protocol was not completed due to development of symptoms. The reproducibility of measurements, calculated by the intra-class correlation coefficient, was relatively high for all indices measured (0.4-0.95) with the exception ofthe proportion of lymphocytes (0.15) and epithelial cells (0.3). The ICC for symptom scores and the CRQ domains ranged between 0.87 and 0.96. In conclusion, sputum induction is safe and the cell and fluid phase mediators repeatable in the investigation of airway inflammation in patients with COPD. VAS symptom scores and the CRQ are reproducible outcome measures in COPD.